FORMATION OF THE METHODOLOGICAL COMPONENT IN FUTURE MUSIC TEACHERS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article describes the aspects of the competency approach in the process of preparing future music teachers for pedagogical activities. In addition, the theoretical foundations of professional competence improvement of future music teachers and the musical competences that the future pedagogue should have in organizing music culture classes by types of activities were analyzed.